The addition of papaya seed flour (Carica papaya) to the growth of ‘Cantang’ hybrid grouper fish (Epinephelus fuscoguttatus >< Epinephelus lanceolatus) - Muhammad Bahrus Syakirin; Linayati Linayati; Tri Yusufi Mardiana; Sisca Yuniarty; Muhammad Zulkham Yahya (Depik, 2022)
This research was carried out to examine the effects of papaya seed flour at different doses on the growth of hybrid groupers and to determine the most optimal dose of papaya seed flour on fish growth. A complete randomized design with 4 treatments and 3 replications was used, which treatments consisted of: treatment A Without papaya seed flour (Control), treatment B with 2.5 grams/kg of papaya seed flour, treatment C with 5 grams of papaya seed flour per kg feed, and treatment D of 7.5 grams papaya seed flour/kg feed. Treatment C was found the most optimal treatment, resulting in an absolute biomass value of 26.97 grams and feed conversion ratio of 1.19. Analysis of variance (ANOVA) of the absolute biomass development of the hybrid grouper obtained an F count of 41.3892 higher than F table of 5%, indicating significant effects on the fish growth. The water quality was set at an ideal level, with temperature ranging between 28-29 0C, pH between 7.0-7.5 and salinity between 30-33 ppt.Keywords:Hybrid groupersPapaya seed flourGrowth